OPTIMIZING FINANCIAL MANAGEMENT FOR STUDENT ENTREPRENEURS: CREATING DECENT WORK AND SUSTAINABLE ECONOMIC GROWTH - Nasution, Hafifah; Sasmi, Aji Ahmadi; Jaya, Tresno Eka; Annisa, Ellis; Hafidz, Ahmad Yassin; Syaqila, Asyifa Putri (International Journal of Engagement and Empowerment (IJE2), 2025)
Student entrepreneurs are a strategic group that plays a crucial role in creating economic independence and new jobs in the future. However, many lack adequate financial management skills. Unplanned financial management, mixing personal and business finances, and a lack of understanding of business legality often hinder the sustainability of student businesses. This community service activity aims to enhance financial literacy and knowledge of business law for student entrepreneurs, enabling them to secure decent work and contribute to sustainable economic growth. The program partners are active students who have or are currently running independent businesses. The main challenges faced are poor business financial management skills and the lack of formal legality due to the absence of a Business Identification Number (BIN). The implementation method included practice-based online training and simulation mentoring using the Online Single Submission (OSS) system. The activity took place on August 8, 2025, via Zoom Meeting and was attended by 22 participants. The results showed an increase in participants' understanding of transaction recording, preparing simple financial reports, and awareness of the importance of business legality. Several participants have also successfully registered for their NIB independently. This activity makes a significant contribution to strengthening the capacity of students as young entrepreneurs who are professional, competitive, and contribute to achieving Sustainable Development Goal 8SDG.